PENGARUH WORK ENGAGEMENT PADA KINERJA BENDAHARA PENGELUARAN DENGAN KEPEMIMPINAN TRANSFORMASIONAL SEBAGAI PEMODERASI - Astuti, Ni Luh Putu; Mimba, Ni Putu Sri Harta; Ratnadi, Ni Made Dwi (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.05.NO.12.TAHUN 2016, 2016)
Research was conducted  to determine the effect on the performance of work engagement treasurer and to determine the ability of transformational leadership moderating influence on the performance of work engagement treasurer BLU Udayana University.The study population was treasurer BLU Udayana University with study respondents were determined by saturation sampling technique with the number of respondents 112. Data source is the primary collected by using a questionnaire that was eligeble validity and reliability. Data is processed once eligible classical assumptions. Data analysis techniques used in the study is a simple linear regression and Moderated Regression Analysis (MRA).. Research model is already qualified test the feasibility of the model and test the coefficient of determination ( adjusted R 2 ) of 37,6 percent. The analysis showed that work engagement positive effect on performance BLU treasurer Udayana University. While variable transformational leadership weaken the influence of work engagement on performance BLU treasurer Udayana University.
Keywords: work engagement, transformational leadership, performance, spending treasurers performance